2017
DOI: 10.1136/bmjopen-2016-014016
|View full text |Cite
|
Sign up to set email alerts
|

In utero and early childhood exposure to secondhand smoke in Taiwan: a population-based birth cohort study

Abstract: ObjectivesThis study provides secondhand smoke (SHS) exposure data in utero and after birth when children were at 18 months, 36 months and 66 months old, and it identifies risk factors for the early childhood SHS among 18-month-old infants living in smoker and non-smoker households.Study designThe data come from the Taiwan Birth Cohort Study, a longitudinal survey of a birth cohort born in 2005. This study used the survey wave when children were 18 months old (n=18 845) for statistical analysis of early childh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 34 publications
1
9
0
1
Order By: Relevance
“…Smoke exposure is responsible for approximately 0.6 million deaths annually and approximately 1% of global disease around the world 1 . The result of a study across 192 countries showed that 40% of children were exposed to secondhand smoke (SHS) 2 and 36% were exposed to SHS in utero 3 . This makes the implications of exposure a potentially significant public health problem.…”
Section: Introductionmentioning
confidence: 99%
“…Smoke exposure is responsible for approximately 0.6 million deaths annually and approximately 1% of global disease around the world 1 . The result of a study across 192 countries showed that 40% of children were exposed to secondhand smoke (SHS) 2 and 36% were exposed to SHS in utero 3 . This makes the implications of exposure a potentially significant public health problem.…”
Section: Introductionmentioning
confidence: 99%
“…In a cohort of 18,845 Taiwanese children aged 18 months, it was found that 62% of these children lived in a household with at least one smoker [48]. Cheng et al [48] further found that 84% of the smokers in the household were fathers of children. Consistently, in Egypt, Abdelati et al [45] also found that more than 50% of 118 pregnant women were exposed to SHS by their spouses.…”
Section: Discussionmentioning
confidence: 98%
“…Individuals' homes may be a major place for SHS exposure for women and children despite public education on reducing tobacco smoke exposure in homes [42,45,46]. Household members are still considered a strong predictor of SHS exposure among women and children [2,45,47,48]. In a cohort of 18,845 Taiwanese children aged 18 months, it was found that 62% of these children lived in a household with at least one smoker [48].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although we have controlled for the major cardiovascular risk factors, information on some risk factors was unavailable in the registry such as body mass index and detailed smoking habits. Less than 5% of women are smokers and obesity is not prevalent in Taiwan [ 35 ]. Clarifying both the dependent and independent variables using ICD9 codes was another limitation.…”
Section: Discussionmentioning
confidence: 99%